2019
DOI: 10.1002/ppul.24610
|View full text |Cite
|
Sign up to set email alerts
|

Role of NT‐proBNP in the prediction of moderate to severe Bronchopulmonary Dysplasia in preterm infants

Abstract: Objective The objective of the study was to determine the clinical utility of brain natriuretic peptide (NT‐proBNP) for prediction of moderate to severe bronchopulmonary dysplasia (BPD). We hypothesized that elevated NT‐proBNP levels at 4 weeks of postnatal age may predict the severity of BPD in preterm infants. Study Design The study design was a prospective observational study. The research team enrolled and followed a cohort of 70 infants with gestational age less than or equal to 30 weeks. The plasma NT‐pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…In another small study ( n = 51) of GA <30 weeks, Harris et al ( 12 ) found that the level of NT-proBNP at 10 days after birth was valuable in predicting severe BPD. Additionally, Khan et al ( 13 ) showed that the NT-proBNP levels on the 28th day after birth were moderately predictive of the severity of BPD in a prospective study. These studies all measured the NT-proBNP levels on a particular day, but the postnatal NT-proBNP levels in newborns are a dynamic process.…”
Section: Introductionmentioning
confidence: 99%
“…In another small study ( n = 51) of GA <30 weeks, Harris et al ( 12 ) found that the level of NT-proBNP at 10 days after birth was valuable in predicting severe BPD. Additionally, Khan et al ( 13 ) showed that the NT-proBNP levels on the 28th day after birth were moderately predictive of the severity of BPD in a prospective study. These studies all measured the NT-proBNP levels on a particular day, but the postnatal NT-proBNP levels in newborns are a dynamic process.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the clinical utility of serum NT-proBNP on day 28 of life to predict moderate to severe BPD. 15 In that study, infants who later developed moderate to severe BPD had higher NT-proBNP levels. Therefore, in addition to the diagnostic value for a cardiopulmonary pathology, we believe that following the NT-proBNP trend may have clinical utility in monitoring disease progression in these infants.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, an upward trend of NT-proBNP beyond the neonatal period may warrant further investigation and monitoring of secondary pulmonary hypertension in those infants. We have previously reported the clinical utility of serum NT-proBNP on day 28 of life to predict moderate to severe BPD 15 . In that study, infants who later developed moderate to severe BPD had higher NT-proBNP levels.…”
Section: More Recently Fritz Et Al Determined Serum Nt-probnp Values Of 118 Preterm Infants Born ≤ 31mentioning
confidence: 99%
See 2 more Smart Citations